Targeting TLR9 agonists to secondary lymphoid organs induces potent immune responses against HBV infection - Irina Ushach; Ren Zhu; Elen Rosler; Rajendra K. Pandey; N. Tilani S. De Costa; Soheil Pourshahian; Qinglin Han; Chris Li; Leonid Beigelman; Sergei M. Gryaznov; Theodore Yun (Elsevier, 2022)
Despite the existence of a prophylactic vaccine against hepatitis B virus (HBV), chronic hepatitis B virus (CHB) infection remains the leading cause of cirrhosis and liver cancer in developing countries. Because HBV persistence is associated with insufficient host immune responses to the infection, development of an immunomodulator as a component of therapeutic vaccination may become an important strategy for treatment CHB. In the present study, we aimed to design a novel immunomodulator with the capacity to subvert immune tolerance to HBV. We developed a lymphoid organ-targeting immunomodulator by conjugating a naturally occurring, lipophilic molecule, α-tocopherol, to a potent CpG oligonucleotide adjuvant pharmacophore. This approach resulted in preferential trafficking of the α-tocopherol-conjugated oligonucleotide to lymphoid organs where it was internalized by antigen-presenting cells (APCs). Moreover, we show that conjugation of the oligonucleotides to α-tocopherol results in micelle-like structure formation, which improved cellular internalization and enhanced immunomodulatory properties of the conjugates. In a mouse model of chronic HBV infection, targeting CpG oligonucleotide to lymphoid organs induced strong cellular and humoral immune responses that resulted in sustained control of the virus. Given the potency and tolerability of an α-tocopherol-conjugated CpG oligonucleotide, this modality could potentially be broadly applied for therapeutic vaccine development.